Entrapment efficiency and drug loading of curcumin nanostructured lipid carrier (NLC) formula - Rabima Rabima; Metri Purnama Sari (Pharmaciana, 2019)
Curcumin is a chemical compound that has low solubility and bioavailability and, for these reasons, limited biological effectiveness. For improvement, the solubility needs to be increased by nanotechnology and nanoparticles, among others. Nanostructured Lipid Carrier (NLC) is a new drug delivery system that offers several advantages, including a significant increase in drug solubility and entrapment efficiency. This study aimed to formulate curcumin into curcumin-loaded NLC preparation and determine its characteristics, absorption efficiency, and drug loading. The formulation used evaporation and solvent diffusion methods with three different concentrations, namely 5%, 10%, and 15%. Spectrophotometry and HPLC were employed to test the absorption efficiency and drug loading capacity.Â  The results showed that the curcumin-loaded NLC preparation containing 10% curcumin had stable characteristics and produced particles sized 17.4 nm with a polydispersity index of 0.574 and zeta potential of -63.43 mV. Based on the spectrophotometry results, the entrapment efficiency was 93.212%, and the drug loading capacity was 0.708%. Meanwhile, the HPLC showed that the entrapment efficiency was 93.007%, and the drug loading capacity was 0.795%.